Upaya Menumbuhkan Kesadaran Hukum Anak melalui Keluarga dalam Perspektif Pendidikan Karakter - Waskito, Yohanes Saing; Suyahman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine efforts to foster children's legal awareness through families from a character education perspective. Families have an important role in shaping children's legal awareness by teaching legal and ethical values, as well as being role models for children. Character education can help children understand their rights and obligations as citizens. The results of this study indicate that families can foster children's legal awareness through character education by teaching legal values, creating a supportive environment, and being role models for children. Thus, this study can contribute to efforts to increase children's legal awareness through families from a character education perspective.